SUPPORTING SOFTWARE COMPREHENSION THROUGH STRUCTURAL AND SEMANTIC ANALYSIS MODULE IN GRAPH- BASED VISUALIZATION - Ardiansyah, Firizky
Software understanding activities are crucial in software development. As software grows and becomes complex, strategies are needed to understand it more efficiently. This study aims to develop structural and semantic analysis module to support program comprehension through program visualization in a graph representation. This module aims to enhance the readability of the visualized graph representation and provide relevant context to aid in interpreting the graph visualization. The structural analysis includes graph clustering and multi-level granularity of the graph. Graph clustering helps identify or investigate the structure of the software